Construction technologies and mechanical effects of the pipe-jacking crossing anchor-cable group in soft stratum - Han, Jianyong; Wang, Jun; Jia, Dongfeng; Yan, Fushun; Zhao, Yue; Bai, Xiaoyu; Yan, Nan; Yang, Guang; Liu, Dong (Frontiers in Earth Science, 2023)
In this study, an open-cut approach using steel-sheet piles and jet grouting piles for waterproofing was proposed to resolve the problem that ordinary pipe-jacking equipment cannot cross areas with existing anchor cables in soft stratum. The case history of a pipe-jacking project of a sewage treatment plant in the Jinan East Railway Station area was investigated. The mechanical properties of steel-sheet piles, horizontal displacement of piles, and ground surface settlement in the anchor-cable crossing area were investigated based on in situ observations. Numerical investigations were performed using the finite element method (FEM). The effects of existing anchor cables on the mechanical behaviors of retaining structures, deformation variation of the ground, and stability of the excavation were studied. The results indicate that the composite supporting structures of steel-sheet piles and jet grouting piles have a positive effect on waterproofing and deformation control in areas with existing anchor cables. When the steel-sheet pile touched the anchor cable during pile jacking, the compressive stress at the pile cap increased rapidly until it reached 62.8 MPa (the maximum pressure provided by the pile-pressing machine), which is twice the pressure under ordinary conditions. The maximum horizontal displacement of the retaining pile, δv, increased linearly with the excavation depth He. Existing anchor structures behind the excavation can restrain the deformation of the ground and retain the structure to a certain extent. The δv value of the pile with existing anchor structures behind is 6.5 mm or approximately 0.01% of the He value, which is 70% of that of the retaining pile without existing anchor structures. “Groove type” ground surface settlements are found on both sides of the excavation. The maximum ground settlements δh are 0.29% He and 0.05% He, respectively. The plastic zone at both sides of the excavation bottom extends to the ground surface with an angle of about 45°. When an excavation fails, the plastic zone range in the ground with existing anchor cables is significantly larger than it is in the ground without anchor cables. The key contribution of this research is to provide an effective and low-budget treatment for pipe-jacking crossing through an anchor-cable group region. The findings from this study also provide industry practitioners with a comprehensive guide regarding the specific applications and mechanical performance of the crossing excavation for obstacle treatment.